Molecular and therapeutic advancements in Capicua (CIC)-rearranged sarcoma - Ponce, Rovingaile Kriska M.; Luck, Cuyler; Okimoto, Ross A. (Frontiers in Cell and Developmental Biology, 2024)
Capicua (CIC)-rearranged sarcomas are an aggressive subset of undifferentiated round cell sarcomas. CIC::DUX4, the proto-typical CIC fusion oncoprotein is associated with rapid clinical progression and chemotherapy resistance leading to poor clinical outcomes. Recent studies have identified additional CIC fusions (CIC::NUTM1, CIC::FOXO4, CIC::LEUTX) that largely retain CIC-binding specificity but leverage C-terminal binding partners (NUTM1, FOXO4, LEUTX) to potentially activate transcriptional programs that drive oncogenesis. Moreover, the recent development of preclinical models to study CIC::DUX4 sarcoma have advanced our understanding of the underlying biological mechanisms and uncovered key dependencies that can be translated into rational therapies. In this review, we will highlight these recent advancements in CIC-rearranged sarcoma biology with a vision for clinical translation to improve patient outcomes.